Criminogenic Effects of the Prison Environment on Inmate Behavior: Some Experimental Evidence - Camp, Scott D. (Crime & delinquency, 2005)
The current study analyzed a subset of the experimental data collected by Berk, Ladd, Graziano, and Back (2003) to test whether different intensities of incarceration make inmates more criminal while incarcerated. There were 561 male inmates whose equivalent classification scores indicated they had the same level of risk to commit institutional misconduct at the time they were incarcerated. One half of these inmates were sent to the lowest security-level prisons in california, and the other one half were sent to prisons one Step down from the highest security level in california. if prisons are criminnogenic. then the probability of misconduct should vary with the security level to which the initiates were assigned. Instead, inmates were equally likely to commit misconduct in prison regardless of whether they were assigned to a Level I (lowest security level) or a Level Ill prison. [ABSTRACT FROM AUTHOR]